Exopolymer particles: microbial hotspots of enhanced bacterial activity in Arctic fast ice (Chukchi Sea) - Meiners, K; Krembs, C; Gradinger, R (Aquatic Microbial Ecology, 2008)
Sea ice is an important structuring element of Arctic marine ecosystems and provides avast low-temperature habitat for ice-associated bacteria. While it is now known that sea icesequesters large amounts of extracellular polymeric substances (EPS) contributing significantly to itsparticulate organic carbon pool, the ecological role of EPS in sea ice is poorly understood. Using insitu incubations combined with a newly developed triple-staining method (Alcian Blue, DAPI, CTC),we determined the number of CTC-reducing (i.e. actively respiring) sea-ice bacteria living freely orattached to gel-like exopolymer particles. Samples were collected at 6 depths from Chukchi Seacoastal fast ice in April, May and June 2003. Concentrations of exopolymer particles ranged between1.8 106 and 149.1 106 particles l1 (average 4.7 106 particles l1) and showed strong vertical gradientswith maximum concentrations at the ice-water interface. Total bacterial numbers (TBN)ranged from 0.18 109 to 8.48 109 cells l1 with an average fraction of 7.4% of actively respiring cells(range 3.0 to 17.2% of TBN). The attached bacterial fraction (range 4.6 to 28.5%, average 15.0% ofTBN) showed a significantly, approximately 4 times higher proportion of actively respiring cells(average 19.6%, range 7.8 to 37.6%) when compared to the free-living fraction that had an averageof 5.4% (range 1.1 to 11.2%) of actively respiring cells. In conclusion, exopolymer particles in sea iceare microbial hotspots of increased bacterial activity able to foster enhanced biogeochemical cycling.